5th International Conference on Time Perspective - Marcinkevičiūtė , Miglė; Lygytė , Augustė; Lukšytė , Aušrinė; Kairys , Antanas; Vaiciukynaite , Egle; Sadauskaitė , Raimonda; Ivleva , Viktorija; Wittmann , Marc (Vilnius University Proceedings, 2021)
Book of abstracts
Keywords: Time perspective; time perception; subjective time; time psychology; international conference on time perspective; conference